The Natural Flavone Acacetin Blocks Small Conductance Ca2+-Activated K+ Channels Stably Expressed in HEK 293 Cells - Chen, Kui-Hao; Liu, Hui; Sun, Hai-Ying; Jin, Man-Wen; Xiao, Guo-Sheng; Wang, Yan; Li, Gui-Rong (Frontiers in Pharmacology, 2017)
The natural flavone acacetin inhibits several voltage-gated potassium currents in atrial myocytes, and has anti-atrial fibrillation effect in experimental atrial fibrillation models. The present study investigates whether acacetin inhibits the Ca2+-activated potassium (KCa) currents, including small conductance (SKCa1, SKCa2, and SKCa3), intermediate conductance (IKCa), and large-conductance (BKCa) channels stably expressed in HEK 293 cells. The effects of acacetin on these KCa channels were determined with a whole-cell patch voltage-clamp technique. It was found that acacetin inhibited the three subtype SKCa channel currents in concentration-dependent manner with IC50 of 12.4 μM for SKCa1, 10.8 μM for SKCa2 and 11.6 μM for SKCa3. Site-directed mutagenesis of SKCa3 channels generated the mutants H490N, S512T, H521N, and A537V. Acacetin inhibited the mutants with IC50 of 118.5 μM for H490N, 275.2 μM for S512T, 15.3 μM for H521N, and 10.6 μM for A537V, suggesting that acacetin interacts with the P-loop helix of SKCa3 channel. However, acacetin at 3-10 μM did not decrease, but induced a slight increase of BKCa (+70 mV) by 8% at 30 μM. These results demonstrate the novel information that acacetin remarkably inhibits SKCa channels, but not IKCa or BKCa channels, which suggests that blockade of SKCa by acacetin likely contributes to its anti-atrial fibrillation property previously observed in experimental atrial fibrillation.